Answer: x = 20
Step-by-step explanation:
Right angle = 90
90 - 47 = 43
43 - 3 = 40
40/2 = 20
Answer:
(A)![x^2+y^2-10x-12y+60=0](https://tex.z-dn.net/?f=x%5E2%2By%5E2-10x-12y%2B60%3D0)
Step-by-step explanation:
The standard form of the equation of a circle is given as:
![(x-5)^2+(y-6)^2=1](https://tex.z-dn.net/?f=%28x-5%29%5E2%2B%28y-6%29%5E2%3D1)
Simplifying the above given equation, we get
![x^2+25-10x+y^2+36-12y=1](https://tex.z-dn.net/?f=x%5E2%2B25-10x%2By%5E2%2B36-12y%3D1)
![x^2+y^2-10x-12y+36+25=1](https://tex.z-dn.net/?f=x%5E2%2By%5E2-10x-12y%2B36%2B25%3D1)
![x^2+y^2-10x-12y+61=1](https://tex.z-dn.net/?f=x%5E2%2By%5E2-10x-12y%2B61%3D1)
![x^2+y^2-10x-12y+60=0](https://tex.z-dn.net/?f=x%5E2%2By%5E2-10x-12y%2B60%3D0)
which is the required general form of the equation.
Hence, option A is correct.
Write the coeeficientes of the polynomial in order:
| 1 - 5 6 - 30
|
|
|
------------------------
After some trials you probe with 5
| 1 - 5 6 - 30
|
|
5 | 5 0 30
-----------------------------
1 0 6 0 <---- residue
Given that the residue is 0, 5 is a root.
The quotient is x^2 + 6 = 0, which does not have a real root.
Therefore, 5 is the only root. You can prove it by solving the polynomial x^2 + 6 = 0.